The Effectiveness of Forgiveness Therapy in Reducing Academic Procrastination Among Junior High School Students: A Gender Perspective - Handayani, Retno Sri; Matulessy, Andik; Rini, Amanda Pasca (Kirana Publisher (KNPub), 2025)
This study aims to examine the effectiveness of forgiveness therapy in reducing academic procrastination among junior high school (JHS) students, as well as to investigate gender-based differences in the effectiveness of the therapy. The research used a quasi-experimental design with a pretest-posttest approach on two groups, male and female students. The forgiveness therapy intervention was conducted over three sessions, with a maximum duration of 120 minutes per session. The results of the analysis showed that forgiveness therapy significantly reduced academic procrastination for both male (t = 4.344; p = 0.012) and female students (t = 9.487; p = 0.001). The average procrastination scores for male students decreased from 61.20 to 51.20, while for female students, it decreased from 58.40 to 55.40. Furthermore, a significant difference was found between the two groups in the level of procrastination reduction (t = 3.012; p = 0.038), with a larger impact on male students. These findings indicate that forgiveness therapy is an effective psychological intervention for reducing academic procrastination, with its effectiveness varying based on gender.